2017
DOI: 10.1192/pb.bp.116.054270
|View full text |Cite
|
Sign up to set email alerts
|

Are men under-treated and women over-treated with antidepressants? Findings from a cross-sectional survey in Sweden

Abstract: Aims and method To examine gender differences in self-reported depression and prescribed antidepressants (ADs). The Hospital Anxiety and Depression Scale was used to assess depression, and information on prescribed ADs was obtained from the Swedish Prescribed Drug Register.Results Depression was reported by 11.7% of the participants (12.3% men and 11.2% women). ADs were prescribed for 7.6% of the participants (5.3% men, 9.8% women). Among men, 1.8% reported depression and used ADs, 10.5% reported depression bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…Although off-label use and overuse are not exactly the same, this agreement is remarkable given the differences in study designs and types of data used [12,13]. Boehlen et al reported a higher proportion of overuse among males which is similar to the pattern observed in our study for off-label use Boehlen, Freigofas, et al 13 , while a survey from Sweden suggested a higher proportion of overtreatment among older women compared to older men [31].…”
Section: Comparison With Other Studiessupporting
confidence: 83%
“…Although off-label use and overuse are not exactly the same, this agreement is remarkable given the differences in study designs and types of data used [12,13]. Boehlen et al reported a higher proportion of overuse among males which is similar to the pattern observed in our study for off-label use Boehlen, Freigofas, et al 13 , while a survey from Sweden suggested a higher proportion of overtreatment among older women compared to older men [31].…”
Section: Comparison With Other Studiessupporting
confidence: 83%
“…Both these observations overlap those reported in the epidemiological literature. 22,61,62 Most respondents were affected by schizophrenic and psychotic spectrum disorders (34%), had suffered from mental disorders for a long time (40% of our respondents For personal use only.…”
Section: Discussionmentioning
confidence: 97%
“…A male–female proportion at 3:5 was reported in a recent study as the incidence rate of pharmacologically treated depression among individuals 15–44 years of age in Denmark [ 32 ]. This could be a sign of selection bias if men are more often treated with antidepressants compared to women; yet, a Swedish survey study on gender differences in self-reported depression and prescribed antidepressants finds men to report depression to a greater extent than women but prescribed antidepressants to a lesser extent; whereas, women are prescribed antidepressants without reporting depression [ 33 ]. Similarly, a Danish study reports men to have lower use of antidepressants compared to women, when in poor mental health [ 34 ].…”
Section: Discussionmentioning
confidence: 99%